Dairy farmers' perceptions of and actions in relation to lameness management - Babatunde, Sadiq Mohammed; Ramanoon, Siti Zubaidah; Shaik Mohamed Mossadeq, Wan Mastura; Mansor, Rozaihan; Syed Hussain, Sharifah Salmah (MDPI, 2019)
Lameness continues to be a welfare and economic issue for dairy cows. However, the consequences of lameness seem to be better understood by veterinarians and related personnel in comparison to dairy farmers. Prompt detection and treatment of lame cows is essential in reducing its negative impact on milk processing systems. To that end, understanding farmers’ perceptions regarding the significance of lameness to dairy cows is vital. One fundamental aspect is the underestimation of lameness prevalence by dairy farmers, which is as a result of different understanding of the problem. The same applies to their decision to treat lame cows and to adopt various detection and management practices. All of these shortcomings contribute to poor cattle welfare and economic losses in dairy production. This review summarizes the results of studies that have investigated dairy farmers’ perceptions of lameness and the associated implications on the wellbeing and productivity of dairy cows. Factors associated with farmers’ attitudes toward claw health and lameness management are also presented. Additionally, economic observations relating to lameness prevention, treatment and the adoption of lameness detection systems are also highlighted. To strengthen these points, interventional programmes requiring farmers’ participation are discussed as a promising approach in answering some of these challenges. A review of the literature indicates both the opportunities and barriers inherent in the tackling the lameness issue from the farmers’ perspectives. Such knowledge is crucial in identifying measures on how to motivate dairy farmers towards proper lameness management.